Genetic Toxicity Effects of Aqueous and Alcoholic Extracts of Alhagi maurorum on Onion (Allium cepa) Root Tip Cells Using PCR Analysis - Jasim , Adnan Owayes (American Journal of Biology and Natural Sciences, 2026)
Medicinal plants play an important role in traditional and modern medicine due to their wide range of pharmacological properties. Despite their therapeutic value, some plant-derived compounds may exhibit cytotoxic or genotoxic effects depending on their chemical composition and concentration (Wink, 2010; Cowan, 1999; Ali et al., 2021). Therefore, evaluating the safety of medicinal plants has become an important component of toxicological research. The Allium cepa assay is widely used as a reliable biological system for detecting cytotoxicity and genotoxicity. Onion root meristematic cells divide rapidly and respond sensitively to chemical exposure (Fiskesjö, 1985; Leme & Marin-Morales, 2009; Silva et al., 2020)., making them suitable indicators of chromosomal damage and DNA alterations. The emergence and disappearance of bundles in the genome of onion plant Allium cepa . In this study, the genetic toxicity of aqueous and alcoholic extracts of Alhagi maurorum was investigated using onion (Allium cepa) root tip cells. Aqueous extract concentrations included 15%, 20%, 25%, 35%, and 45%, while alcoholic extract concentrations included 2%, 3%, 4%, 6%, and 8%. Polymerase Chain Reaction (PCR) analysis was applied to detect possible DNA alterations associated with exposure to these plant extracts (Williams et al., 1990; Atienzar & Jha, 2006; Iqbal et al., 2020).